Microstructural, phase formation, and superconducting properties of bulk YBa2Cu3Oy superconductors grown by infiltration growth process utilizing the YBa2Cu3Oy + ErBa2Cu3Oy + Ba3Cu5O8 as a liquid source - Kamarudin, Aliah Nursyahirah; Awang Kechik, Mohd Mustafa; Miryala, Muralidhar; Pinmangkorn, Sunsanee; Murakami, Masato; Chen, Soo Kien; Baqiah, Hussein; Ramli, Aima; Lim, Kean Pah; Shaari, Abdul Halim (MDPI, 2021)
The infiltration growth (IG) process is well-known as the most established technique consisting of Y2BaCuO5 (Y211) precursor powders and liquid phases toward the fabrication of bulk YBa2Cu3Oy (Y123) superconductor for high field industrial applications. We have reported the fabrication of Y123 bulks using this technique at various ratios of liquid phase source. In this study, the use of liquid phase source toward the infiltration growth of bulk Y123 superconductors at different ratios of Y123 and ErBa2Cu3Oy (Er123) mixed with Ba3Cu5O8 (Y035) was investigated to control the Y211 secondary phase content in bulk Y123 samples. The liquid phase content was optimized by varying the mass. The sample fabricated using Y123 liquid phase (Y1Er0) showed the onset of critical temperature Tc-onset = 91.85 K. Tc-onset slightly decreased with the addition of Er123. Microstructure analysis revealed a uniform distribution of Y211 secondary phase particles in the Y123 matrix. The Y1Er0 sample had the smallest of Y211 particle size among the samples with average size of 0.992 μm. The formation of this smaller-sized Y211 particles with uniform distributions that act as an effective pinning center, had improved the critical current density, Jc of the sample Y1Er0 at 77 K with H//c-axis having the highest Jc 54.15 kA/cm2 and 11.45 kA/cm2 in self-field and 2 T, respectively. The binary mixed of rare earth superconductors (Y123 + Er123) used in the liquid phase could be used to further improve the superconducting properties of Y123 single grains.